Adapted physical education and sport - Winnick, Joseph P.; Porretta, David L. (Human Kinetics, 2017)
The field of adapted physical education and sport has undergone numerous changes in recent years. This new edition of Adapted Physical Education and Sport will help readers stay on top of those changes and, in doing so, provide the highest-quality physical education and sport opportunities for students with disabilities.